Dynamic hysteresis and scaling behavior of hard lead zirconate titanate bulk ceramics - R. Yimnirun (2018)
The scaling relation of ferroelectric hysteresis area 〈A〉 against frequency f and field amplitude E0 for the saturated loops of the hard lead zirconate titanate bulk ceramic takes the form of 〈A〉 f-0.28 E00.89, while that for the minor loops takes the form of 〈A〉 f-0.43 E03.19. In both cases, the scaling relations are similar to those of its soft counterpart. This indicates that the dynamic behaviors and scaling relations in bulk ceramics are mainly governed by the domain states and structures, while the distinct types of complex defects contribute mainly to the difference in the coercive field observed in hard and soft ceramics. © 2007 American Institute of Physics.